Leukotriene D4 nasal provocation test: Rationale, methodology and diagnostic value - ZHU, ZHENG (Exp Ther Med, 2016)
Cysteinyl leukotrienes (LT) play a vital role in the pathogenesis of allergic rhinitis (AR), but few studies have investigated the nasal mucosal physiological response to LTs in AR patients. The aim of the present study was to establish the methodology and investigate the diagnostic value and safety of a leukotriene D4 (LTD4) nasal provocation test. LTD4 nasal provocation tests were performed in 26 AR patients and 16 normal control subjects. Nasal airway responsiveness was assessed by calculating the concentration of LTD4 required to cause a 60% increase in nasal airway resistance (PC(60)NAR-LTD4), which was measured using rhinomanometry and a composite symptom score. Receiver operating characteristic (ROC) curve was applied to evaluate the diagnostic value of LTD4 nasal provocation test, and adverse events were recorded. The study protocol was registered with the U.S. National Institutes of Health (https://clinicaltrials.gov/ct2/show/NCT01963741). PC(60)NAR-LTD4 in AR was significantly lower compared with that of normal controls [8.36 (IQR, 10.00) vs. 17.00 (IQR, 0.00) µg/ml, P=0.005]. Composite symptom score was higher in AR as compared with normal controls (1.19±0.94 vs. 0.12±0.50, P<0.001). The symptom scores included sneezing (0.12±0.34 vs. 0.00±0.00, P=0.149), rhinorrhea (0.79±0.66 vs. 0.06±0.25, P<0.001) and chemosis or itching of the eyes (0.06±0.25 vs. 0.21±0.42, P=0.216). High diagnostic value was indicated by the ROC [AUC: 0.822, 95%CI (0.665, 0.961)]. No serious adverse events were observed. Thus, the present results indicate that AR patients exhibited nasal hyperactivity to LTD4, and the established procedure of LTD4 nasal provocation testing is effective and safe for use in the diagnosis of AR.